Knowledge Production and Contradictory Functions in African Higher Education - Nico Cloete (African Higher Education Dynamics Series, 2015)
This volume brings together excellent scholarship and innovative policy discussion to demonstrate the essential role of higher education in the development of Africa and of the world at large. Based on deep knowledge of the university system in several African countries, this book will reshape the debate on development in the global information economy for years to come. It should be mandatory reading for academics, policy-makers and concerned citizens, in Africa and elsewhere." - Manuel Castells, Professor Emeritus, University of California at Berkeley, Laureate of the Holberg Prize 2012 and of the Balzan Prize 2013